2006
DOI: 10.1111/j.1478-5153.2006.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Correcting arterial blood gases for temperature: (when) is it clinically significant?

Abstract: Interpreting arterial blood gases (ABGs) is a common practice in intensive care units. The use of the temperature correction facility, however, is not standardized, and the effects of temperature correction on the ABG result may affect the overall management of the patient. The aim of this study was to discuss the significance of temperature correction. Current practice in the UK and Australia is discussed along with a review of physiological principles of oxygenation and acid-base balance. The alpha-stat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…This could account in part for the different conclusions of these 2 studies. Temperature correction of ABG results is a controversial issue in human medicine 14,15 and is likely unnecessary when the patient's temperature is measured within 1°C of 37°C 14 which was the case of the horses in our study (mean AE SD, 37.3 AE 0.3°C; range, 36.6-38°C). Studies in geriatric dogs have not shown a significant difference in PaO 2 or PaCo 2 results compared to younger dogs.…”
Section: Discussionmentioning
confidence: 83%
“…This could account in part for the different conclusions of these 2 studies. Temperature correction of ABG results is a controversial issue in human medicine 14,15 and is likely unnecessary when the patient's temperature is measured within 1°C of 37°C 14 which was the case of the horses in our study (mean AE SD, 37.3 AE 0.3°C; range, 36.6-38°C). Studies in geriatric dogs have not shown a significant difference in PaO 2 or PaCo 2 results compared to younger dogs.…”
Section: Discussionmentioning
confidence: 83%
“…This is particularly important in the context of blood gas assessment of a hypo-or hyperthermic animal, where the consensus is that temperature correction should be applied (Jones et al, 1989;Bacher, 2005;Higgins, 2016). The neces-3211 sity for temperature correction within the euthermic range has not be determined for animals and is deemed unnecessary in humans (Bisson and Younker, 2006;Goldsmith et al, 2016); therefore, the effect of the absence of temperature correction in our study cannot be defined.…”
Section: Discussionmentioning
confidence: 94%
“…34 The resulting decrease in oxygen release to tissues is counterbalanced by decreased tissue oxygen demand at lower temperatures, and consequently tissue oxygen content appears to be maintained. 35 Studies in neonates and pediatric patients have shown that transcutaneous pulse oximetry measurements remain accurate if the skin temperature is >29 °C or core temperature is>31 °C.…”
Section: Physiologic Effects Of Hypothermiamentioning
confidence: 99%